2010
DOI: 10.1038/hr.2010.39
|View full text |Cite
|
Sign up to set email alerts
|

Very low-grade albuminuria reflects susceptibility to chronic kidney disease in combination with cardiovascular risk factors

Abstract: Low-grade albuminuria has been proposed as a cardiovascular risk factor that is below the conventional cut-off point for microalbuminuria, which has been previously identified as a marker for cardiovascular disease and chronic kidney disease (CKD). Metabolic syndrome has also been shown to be related with microalbuminuria and CKD. We assessed the relationship among low-grade albuminuria, CKD and metabolic syndrome among 5998 non-diabetic subjects. The subjects were divided into six groups: subjects with urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The prevalence of CKD increased with increasing UACR values and greater numbers of metabolic syndrome characteristics [16]. This, in turn, was associated with a decreased UACR cut-off point and the increased prevalence of CKD.…”
Section: Uacr Cut-off Values For Diseases Associated With Diabetesmentioning
confidence: 89%
See 2 more Smart Citations
“…The prevalence of CKD increased with increasing UACR values and greater numbers of metabolic syndrome characteristics [16]. This, in turn, was associated with a decreased UACR cut-off point and the increased prevalence of CKD.…”
Section: Uacr Cut-off Values For Diseases Associated With Diabetesmentioning
confidence: 89%
“…To date, many studies have reported UACR cut-off values for diseases that are associated with diabetic diabetes, e.g., MA cut-offs of 19.25 mg/g Cr [19] for hypertension; 10.7 mg/g Cr [20], 15.6 mg/g Cr [21], 10.7 mg/g Cr [22], and 10.0 mg/g Cr [23] for diabetic retinopathy (DR); and 4.8 mg/g Cr [6] for metabolic syndrome. However, only four studies that investigated the cut-off values for type 2 diabetes [15], CKD [16], and DN [17,18] have been conducted.…”
Section: Uacr Cut-off Values For Diseases Associated With Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…[81][82][83] A total of 66 studies, comprising 699 065 CKD patients and 11 109 003 participants, were finally included in the meta-analysis. Among the included studies, 43 were from the East Asian populations 8,9,[22][23][24][25][27][28][29]33,[35][36][37][38][39][40][41]43,44,51,52,[55][56][57][58][59]62,[65][66][67]69,[71][72][73][74][75][76][77][78][79][80]82,83 and 23 were from non-East Asian populations. 12,20,21,26,[30...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Palaniappan et al demonstrated a higher rate of microalbuminuria in men and women with MetS than in healthy controls [20]. The cutoff point of the urinary albumin-to-creatinine ratio varied in subjects with various CVD risk profiles, and even low-grade albuminuria below the conventional cutoff point for microalbuminuria was associated with increased prevalence of CKD [21]. Kurella et al performed a longitudinal cohort study and found a higher rate of CKD in MetS even after adjustment for subsequent development of diabetes and hypertension, suggesting that MetS is independently associated with an increased risk for incident CKD in nondiabetic adults [22].…”
Section: Epidemiology Of Mets and Ckdmentioning
confidence: 99%